MONETARY POLICY: MANY QUESTIONS STILL REMAIN - M. V. Yershov (Финансы: теория и практика, 2017)
The ruble economy must be shaped by a correct monetary policy; therefore, ruble assets must be estimated more realistically (which means they should cost more). „When they try to convince us that the weak ruble is better for us it seems absurd and akin to the saying that the more lightweighted is the salary we receive or are the rubles placed with our bank accounts or in the purse and the less we can buy for them it is advantageous for us. We are setting up the ruble-, not the dollar-based economy, and the more expensive will be ruble assets owned by the households and business, the richer they will be. Of course, mechanisms are needed to protect the domestic market and promote exports. But who said that they are all confined to the exchange rate? After all, its impact has often opposite venues, and the devaluation stimulates primarily the export of raw materials increasing the dependence of our economy on the world market…” (from an interview with „Bankovsky Ryad”).